2020
DOI: 10.1111/apt.15998
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: effectiveness of anti‐inflammatory therapy in immune checkpoint inhibitor‐induced enterocolitis

Abstract: Summary Background Immune checkpoint inhibitors have revolutionised cancer treatment, but at the cost of off‐target immune‐mediated organ damage. This includes checkpoint inhibitor‐induced enterocolitis which frequently requires hospitalisation and may be life‐threatening. Empiric treatment typically includes corticosteroids and infliximab, although no large‐scale studies have confirmed their effectiveness. Aim To investigate the effectiveness of anti‐inflammatory therapy in checkpoint inhibitor‐induced entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…In corticosteroid refractory disease, which occurs in over a third of patients, infliximab (IFX), an anti-tumor necrosis factor (TNF) monoclonal antibody, is recommended. 15 These guidelines are predominantly based on expert opinion, and to date, there is a paucity of data informing the appropriate institution of secondline therapies such as IFX. In a recent meta-analysis evaluating anti-inflammatory therapies in CPI-induced enterocolitis, data pooled from 17 studies across 333 patients 15 found that IFX was effective in 81% (95% CI 73% to 87%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In corticosteroid refractory disease, which occurs in over a third of patients, infliximab (IFX), an anti-tumor necrosis factor (TNF) monoclonal antibody, is recommended. 15 These guidelines are predominantly based on expert opinion, and to date, there is a paucity of data informing the appropriate institution of secondline therapies such as IFX. In a recent meta-analysis evaluating anti-inflammatory therapies in CPI-induced enterocolitis, data pooled from 17 studies across 333 patients 15 found that IFX was effective in 81% (95% CI 73% to 87%).…”
Section: Introductionmentioning
confidence: 99%
“…15 These guidelines are predominantly based on expert opinion, and to date, there is a paucity of data informing the appropriate institution of secondline therapies such as IFX. In a recent meta-analysis evaluating anti-inflammatory therapies in CPI-induced enterocolitis, data pooled from 17 studies across 333 patients 15 found that IFX was effective in 81% (95% CI 73% to 87%). There was evidence that timely initiation of IFX within 10 days of onset of symptoms led to significantly fewer hospitalizations, fewer corticosteroid taper failures, shorter courses of corticosteroid treatment and shorter duration of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Two independent studies in different tumour settings, identi ed impaired survival in steroid exposed patients 15,16 . Treatment outcomes with biological therapies, such as anti-TNFα drugs are also heterogeneous 17 , especially if robust outcome measures are used. Not only do many patients fail to achieve steroid-free remission, but side effects also including severe infections were common 18 .…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with severe symptoms should receive systemic corticosteroids or infliximab, an anti-TNFα antibody. Although there is limited data available from prospective studies with a large sample size, Ibraheim et al reported in the meta-analysis of 39 studies that corticosteroid efficacy was 59% [20]. Additionally, the response to infliximab in patients who are refractory or intolerant to corticosteroids was reported to be 81%, with 1-3 infliximab doses in most cases.…”
Section: Introductionmentioning
confidence: 99%